Taking on colds - Borgert-Spaniol, Megan, 1989- (2021)
"This title examines viruses, bacteria, fungi and protozoa with a focus on rhinoviruses and coronaviruses from how they infect the body and cause colds and are spread from person-to-person, the body's immune response, to symptoms and treatment, and when to see a doctor. Secondary complications are also covered. A list of healthy habits is included to help readers combat disease."--
Your amazing body -- When a cold attacks -- All about colds -- Catching a cold -- Your immune system -- Cold season -- Do you have a cold? -- Cold vs. flu -- No vaccine -- Getting better -- When to see a doctor -- Cold complications -- Healthy habits -- Glossary -- Online Resources -- Index.
Includes index.
Ages 7-10
Keywords: Cold (Disease) -- Juvenile literature; Cold (Disease) -- Prevention -- Juvenile literature; Health behavior -- Juvenile literature; Immunology -- Juvenile literature; Hygiene -- Juvenile literature; Cold (Disease); Cold (Disease) -- Prevention; Health behavior; Immunology; Cleanliness; Cold (Disease); Cold (Disease) -- Prevention; Health behavior; Hygiene; Immunology; Juvenile works